Peningkatan Kemampuan Motorik Kasar melalui Kegiatan Senam Irama - Anik Wijayanti (Universitas Lampung, 2020)
This study aims to describe the increase in gross motor skills through rhythmic gymnastics in the Nurul Iman Padas Ngawi playgroup. The research method used is collaborative classroom action research using a modified model of Kemmis and Mc Taggart which includes four stages, namely planning, action, observation, and reflection. The research subjects were 12 children of the Nurul Iman Padas Ngawi Play Group, consisting of 3 boys and 9 girls. Data collection techniques are carried out through observation, interviews, and documentation study. The data analysis technique in this research is qualitative and quantitative data analysis. The success indicator determined is if at least 75% or 9 children out of 12 have gross motor skills with very well developed criteria. The results of this study indicate that the process of implementing rhythmic gymnastics activities in improving gross motor skills of children in the Play Group Nurul Iman Padas Ngawi. Rhythmic gymnastics can improve children's gross motor skills by 92%.Keywords: Gross Motor Skills, Activities, Rhythmic Gymnastics, Play Groups, Action ResearchDOI: http://dx.doi.org/10.23960/jiip.v2i1.21785